Pro-inflammatory macrophages suppress HIV replication in humanized mice and ex vivo co-cultures - Baroncini, Luca; Muller, Christina K. S.; Kadzioch, Nicole P.; Wolfensberger, Rebekka; Russenberger, Doris; Bredl, Simon; Mlambo, Tafadzwa; Speck, Roberto F. (Frontiers in Immunology, 2024)
Very little is known about the role of macrophages as immune mediators during natural HIV infection. Humanized mice are a highly valuable in vivo model to study HIV pathogenesis. Still, the presence of murine mononuclear phagocytes in these models represents a significant limitation for the study of their human counterpart. Therefore, we developed a novel humanized mouse model, iHMD-NSG, which enables selective depletion of human myeloid cells at a time point of our choosing. These inducible human myeloid cell depletion (iHMD) mice showed specific human myeloid cell depletion with no adverse events for the animals. We used this model to show that human mononuclear phagocytes restrict HIV replication in vivo, which is accompanied by an increase in antiviral cytokines and chemokines. We found a similar HIV-inhibitory effect of macrophages in an ex vivo co-culture system, which was mediated by soluble factors. Transcriptomic data revealed the upregulation of antiviral cytokines and chemokines in macrophages of these co-culture experiments. RNA sequencing CD4+ T-cells showed cellular activation, up-regulation of HIV restriction factors and the downregulation of DNA transcription and RNA translation in the presence of macrophages. This work describes a novel role of macrophages as effector cells acting against HIV replication and disease progression.